PENGARUH DISIPLIN KERJA DAN FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN MNCTV BAGIAN PRODUKSI - Budi Sayoto; Herry Winarto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This study aims to examine the effect of work discipline and work facilities on employee work productivity, either partially or simultaneously on MNC TV Production Section. The research method used is descriptive and quantitative research method with a sample of 75 respondents. Data collected by using method is multiple linear regression analysis, double correlation and coefficient of determination. Test the hypothesis (Test F and Test t).The results showed that work discipline and work facilities have a significant effect on increasing productivity of employee of MNC TV Production Division.